Irregularity as a unifying principle of the novel trilogy by Stanislav Komarek - Antos, Matej (Bohemica Olomucensia, 2020)
The study focuses on the works of prose by contemporary Czech philosopher, biologist and essayist Stanislav Komarek, specifically on three novels, sometimes referred to as "irregular trilogy": Opslstisova nadace (Opslstis Foundation, 2002), Cerny domecek (Black House, 2004) and Mandarini (Mandarins, 2007). With the use of analytical-interpretive probes the study aims to find out and prove whether the principle of irregularity itself might work as a connecting link between the texts on different levels, especially regarding the genre structure, fictional setting and the way how aluctions and mystifications are utilized within the texts.
Keywords: Stanislav Komarek; irregular trilogy; contemporary Czech prose; literary analysis; postmodern literature